The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.2337/dc12-1596
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Effects of Bariatric Surgery in Patients With Moderate Obesity and Type 2 Diabetes

Abstract: OBJECTIVETo evaluate the effects of two bariatric procedures versus intensive medical therapy (IMT) on β-cell function and body composition.RESEARCH DESIGN AND METHODSThis was a prospective, randomized, controlled trial of 60 subjects with uncontrolled type 2 diabetes (HbA1c 9.7 ± 1%) and moderate obesity (BMI 36 ± 2 kg/m2) randomized to IMT alone, IMT plus Roux-en-Y gastric bypass, or IMT plus sleeve gastrectomy. Assessment of β-cell function (mixed-meal tolerance testing) and body composition was performed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
182
0
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(199 citation statements)
references
References 32 publications
5
182
0
10
Order By: Relevance
“…Two years after surgery, insulin sensitivity was significantly increased by 2.7-fold from baseline and b-cell function (disposition index) was increased 5.8-fold (22). The reduction in abdominal (truncal) fat was inversely correlated with the b-cell function.…”
mentioning
confidence: 71%
“…Two years after surgery, insulin sensitivity was significantly increased by 2.7-fold from baseline and b-cell function (disposition index) was increased 5.8-fold (22). The reduction in abdominal (truncal) fat was inversely correlated with the b-cell function.…”
mentioning
confidence: 71%
“…The reason for this remains a controversy, as studies have shown that the beneficial effects of RYGB on T2D are weight loss independent (e.g., [3]), while others suggest that they result from reduced food intake (4). Clinical studies have shown that RYGB has greater effect on remission of T2D than, for example, vertical sleeve gastrectomy, despite similar weight loss (5). This is in support of weight-independent factors underlying the resolution of T2D upon RYGB.…”
mentioning
confidence: 97%
“…In a prespecified substudy analysis of beta-cell function, insulin sensitivity, and body composition in a subgroup of patients, we found that at 2 years, gastric bypass was superior to sleeve gastrectomy with respect to insulin secretion, insulin sensitivity, and relative reduction in truncal fat as compared with subcutaneous fat. 20 Most clinical guidelines and insurance coverage for bariatric surgery limit access to the surgery to patients with a BMI of 35 or more, presumably because of insufficient studies evaluating outcomes in patients with a BMI of less than 35. In our study, 49 of 137 patients (36%) had a BMI of 27 to 34, and these patients had an improvement in glycemic control and durability that was similar to that in patients with a BMI of 35 or more.…”
Section: Discussionmentioning
confidence: 99%